A marine Chlamydomonas sp. emerging as an algal model. Issue 1 (22nd November 2020) - Carrasco Flores, David; Fricke, Markus; Wesp, Valentin; Desirò, Daniel; Kniewasser, Anja; Hölzer, Martin; Marz, Manja; Mittag, Maria
Abstract : The freshwater microalga Chlamydomonas reinhardtii, which lives in wet soil, has served for decades as a model for numerous biological processes, and many tools have been introduced for this organism. Here, we have established a stable nuclear transformation for its marine counterpart, Chlamydomonas sp. SAG25.89, by fusing specific cis ‐acting elements from its Actin gene with the gene providing hygromycin resistance and using an elaborated electroporation protocol. Like C. reinhardtii, Chlamydomonas sp. has a high GC content, allowing reporter genes and selection markers to be applicable in both organisms. Chlamydomonas sp. grows purely photoautotrophically and requires ammonia as a nitrogen source because its nuclear genome lacks some of the genes required for nitrogen metabolism. Interestingly, it can grow well under both low and very high salinities (up to 50 g · L ‐1 ) rendering it as a model for osmotolerance. We further show that Chlamydomonas sp. grows well from 15 to 28°C, but halts its growth at 32°C. The genome of Chlamydomonas sp. contains some gene homologs the expression of which is regulated according to the ambient temperatures and/or confer thermal acclimation in C. reinhardtii . Thus, knowledge of temperature acclimation can now be compared to the marine species. Furthermore, Chlamydomonas sp. can serve as a model for studying marine microbial interactions and for comparing mechanisms in freshwater and marine environments. Chlamydomonas sp. was previously shown to be immobilized rapidly by a cyclic lipopeptide secreted from the antagonistic bacterium Pseudomonas protegens PF‐5, which deflagellates C. reinhardtii .